Symbiont-driven sulfur crystal formation in a thiotrophic symbiosis from deep-sea hydrocarbon seeps - Eichinger, Irmgard; Schmitz-Esser, Stephan; Schmid, Markus; Fisher, Charles R; Bright, Monika (ENVIRONMENTAL MICROBIOLOGY REPORTS, 2014)
The siboglinid tubeworm Sclerolinum contortum symbiosis inhabits sulfidic sediments at deep-sea hydrocarbon seeps in the Gulf of Mexico. A single symbiont phylotype in the symbiont-housing organ is inferred from phylogenetic analyses of the 16S ribosomal ribonucleic acid (16S rRNA) gene and fluorescent in situ hybridization. The phylotype we studied here, and a previous study from an arctic hydrocarbon seep population, reveal identical 16S rRNA symbiont gene sequences. While sulfide is apparently the energy source for the symbionts (and ultimately the gutless host), both partners also have to cope with its toxicity. This study demonstrates abundant large sulfur crystals restricted to the trophosome area. Based on Raman microspectroscopy and energy dispersive X-ray analysis, these crystals have the same S8 sulfur configuration as the recently described small sulfur vesicles formed in the symbionts. The crystals reside adjacent to the symbionts in the trophosome. This suggests that their formation is either extra-or intracellular in symbionts. We propose that formation of these crystals provides both energy-storage compounds for the symbionts and serves the symbiosis by removing excess toxic sulfide from host tissues. This symbiont-mediated sulfide detoxification may have been crucial for the establishment of thiotrophic symbiosis and continues to remain an important function of the symbionts.
Keywords: ROV Jason (Remotely Operated Vehicle)